Spatial externality of railway service improvement - To understand the Japanese inter-regional transportation service improvements - Makoto Tsukai; Makoto Okumura (European Regional Science Association (ERSA), 2005)
Multimodal policy between railway and airlines is of importance in providing seamless transportation service to inter-regional passengers. However, it is difficult to make coordination among the railway and airline service suppliers, especially when they are fiercely competing for the share in passenger market in the target OD. Inter-regional transportation in Japan, fierce competitions are observed between Japan Railway companies and airlines, especially after the 1990 fs deregulation of the airline entrance; the number of new air service are parallel to the conventionally profitable railway service. Regardless to railway service improvements such as speed-ups, increase of frequency and special tickets of bargain fares, the number of airline passengers has been increased in the middle to long distant regions, while railway passengers continuously decreased. Such consequence would be brought by the multimodal route which has an airline link as the trunk line, and railway links as the access or egress service, considering inter-regional passenger behaviors. In other words, the improvement of railway service of middle to long distance would simultaneously and inevitably improve the short distant railway service, which can be used as the access line to airport. This phenomenon can be called the spatial externality of railway network. Spatial externality much strongly appears in railway network, comparing to airlines. If the above consideration is valid, inter-regional transportation market would not be efficient without considering the unintended multimodal use. This study purposes to clarify the existence and effects of spatial externality of railway service from investigation of longitudinal change in inter-regional transportation service and demand in Japan. The LOS of multimodal routes are calculated by the k-th shortest path algorithm which gives alternative routes to the shortest. In order to assess the LOS for each OD, the mode choice model is estimated, and passenger utilities of ODs are calculated. The results are aggregated for each distance range of ODs, and compared the LOS improvement measured by estimated utilities with the number of passengers of railway and of airlines. Implications for regional transportation administration are finally made.
Keywords: 330